Analysis Factors of the Intention of Postpartum Women using Long-Acting Reversible Contraceptive Based on the Theory of Planned Behavior - Tantya Edipeni Putri; Retnayu Pradanie; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2021)
Introduction:The use of Long-Acting Reversible Contraceptive (LARC) in postpartum women is still low even though the government recommends an effective method to decrease population growth. Attitude, subjective norm, and perceived behavioral control are background factors that shape people's intentions in displaying behavior. This study aimed to analyze the correlation between attitude, subjective norm, and perceived behavioral control with postpartum women's intentions using LARC.Methods: This study used a descriptive correlational design with a cross-sectional approach. The populations were postpartum women ≤ 42 days in Tambaksari Sub-District Surabaya. The inclusion criteria were postpartum women who had not become KB acceptors and the exclusion criteria for postpartum women with widow status.  The samples were 84 people that met using a purposive sampling technique. Data were collected with a questionnaire consisting of demographic data, attitude, subjective norm, perceived behavioral control, and intentionand analyzed using spearmen's rho test with a significance level of 0.05.Results: The result showed that attitude (p=0.000 r=0.604) , subjective norm (p=0.000 r=0.610), and perceived behavioral control (p=0.000 r=0.608) had significant correlation with intentions.Conclusion: The positive attitude, good subjective norm support, and robust perceived behavioral control give high intentions using LARC in postpartum women. The recommendations for future researchers are expected to conduct a comparative study of the behavior of choosing LARC and Non-LARC in postpartum women.